Cloning and computer analysis of the promoter region of the legumin-like storage protein gene from buckwheat, Fagopyrum esculentum Moench - Milisavljević Mira; Konstantinović Miroslav M.; Brkljačić Jelena M.; Maksimović Vesna R. (Archives of Biological Sciences, 2004)
Using the modified 5’-RACE approach, a fragment containing the 955 bp long 5’- regulatory region of the buckwheat storage globulin gene (FeLEG1) has been amplified from the genomic DNA of buckwheat. The entire fragment was sequenced and the sequence analyzed by computer prediction of cis-regulatory elements possibly involved in tissue specific and developmentally controlled seed storage protein gene expression. The promoter obtained might be interesting not only for fundamental research, but also as a useful tool for biotechnological application.